Problematika Pelaksanaan Pembelajaran Biologi di Kelas X SMA Negeri 3 Bulukumba - Berti, Elisa; Syamsudduha, St.; Suhardiman, Suhardiman (Al Asma: Journal of Islamic Education, 2025)
The implementation of the new curriculum, particularly diagnostic assessment and differentiated learning, often faces challenges. This descriptive qualitative study aims to map the challenges and solutions for implementing diagnostic assessments, differentiated learning, and formative assessments in biology for grade 10 students at SMA Negeri 3 Bulukumba. The research subjects (biology teachers and curriculum representatives) were selected using purposive sampling. Data were analyzed using the Miles and Huberman model. The results showed that the main challenges of diagnostic assessment were difficulties in implementing the results and time constraints. Problems with differentiated learning included teacher unfamiliarity, time constraints, and difficulties in grouping students. In formative assessment, challenges included difficulties in preparing instruments and ensuring the validity of student responses. The solutions implemented by teachers focused on optimizing Subject Teachers' Deliberation (MGMP), using varied media, emphasizing emotional approaches, enhancing competency, and integrating assessment into learning scenarios. The implications of this study underscore the need for ongoing training and systemic support to enable teachers to effectively address the challenges of curriculum implementation.